2012
DOI: 10.4236/psych.2012.31003
|View full text |Cite
|
Sign up to set email alerts
|

Academic Procrastinators and Their Self-Regulation

Abstract: Previous procrastination research has provided considerable support for procrastination as a failure of self-regulation. However, procrastination has rarely been examined in relation to models of self-regulated learning. The purpose of this study was to understand the motives and reasons for academic procrastination from a self-regulated learning perspective. The current study employed a mixed-methods design in which participants completed several survey instruments of academic procrastination, self-regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
55
0
22

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 44 publications
(68 reference statements)
12
55
0
22
Order By: Relevance
“…Similarly Thompson (1999) also indicated that individuals who are doubtful about their abilities to complete a task successfully try to protect their self-esteem by procrastinating. Much research has pointed out the relation of procrastination with self-esteem (Balkis & Duru, 2012;Ferrari & Diaz-Morales, 2007;Park & Sperling, 2012;Pychyl, Coplan, & Reid, 2002). Briefly, high level of procrastination is supposed to be related with low level of self-esteem.…”
Section: Procrastination and Self-esteemmentioning
confidence: 99%
“…Similarly Thompson (1999) also indicated that individuals who are doubtful about their abilities to complete a task successfully try to protect their self-esteem by procrastinating. Much research has pointed out the relation of procrastination with self-esteem (Balkis & Duru, 2012;Ferrari & Diaz-Morales, 2007;Park & Sperling, 2012;Pychyl, Coplan, & Reid, 2002). Briefly, high level of procrastination is supposed to be related with low level of self-esteem.…”
Section: Procrastination and Self-esteemmentioning
confidence: 99%
“…A low self-esteem corresponds to a high level of procrastination. In this case teachers play an important role to manage the self-regulation teaching in the classroom (Asikhia 2010;Babadogan 2010;Behrozi, Yeilagh, & Mansourian, 2013;Klassen, Krawchuck, & Rajani, 2008;Motie, Heidari, & Sadhegi, 2013;Park & Sperling, 2012;Wolters, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The internal ones are: (1) personality-related which includes negative self-image, avoidance, and perfectionism (Zeenath & Orcullo, 2012;Patrzek, Grunschel, & Fries, 2012;Procee, Kamphorst, Wissen, & John-Jules, 2013;Pychyl, Coplan, & Reid, 2002;Saleem & Rafique, 2012), (2) competence-related which covers lack of knowledge, regulation of low self-esteem, and lack of study skills, (3) affective which refers to anxiety, frustration, boredom, feelings of anxiety, shame, and guilt (Deniz, Traz, & Aydogen, 2009;Haghbin, Mccaffrey, & Phychyl, 2012;Vahedi, Farrokhi, Gahramani, & Issazadegan, 2012;Haycock, McCarthy, & Skay, 1998), (4) cognitive which concerns on fear, lack of internal motivation, and failure of self-regulation (Park & Sperling, 2012;Asri, 2015), (5) learning history which consists of behavioral learning and negative learning experience, (6) physical and mental health, (7) perception of the characteristics of academic assignments viewing the task as an enemy, or as difficulty, or otherwise it is perceived as important to work with (Procee et al, 2013), (8) lack of the scale of priorities, (9) poor time management skills, and (10) the selection of coping strategies used (Procee et al, 2013;Asikhia, 2010;Tsai, Shen, & Lee, 2011;Seperiah & Lotf, 2011). While the external ones cover school-related matters such as the quality of teachers, peer influences, and external conditions of the school (Zeenath & Orcullo, 2012;Patrzek et al, 2012) and the style of parenting (Pychyl et al, 2002;Zakeri, Esfahani, & Razmjoee, 2013;Vahedi & Mortazanajad 2009;Milgram & Toubiana, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…2007;Steel 2007;Steel, Ferrari 2013). Natomiast jako przyczyny prokrastynacji akademickiej wskazywane są niekorzystne, ale typowe dla studenckiego stylu życia, zachowania (Park, Sperling 2012;Eerde 2003). Zalicza się do nich preferowanie wykonywania zadań atrakcyjnych nad ważnymi i pilnymi, odkładanie zadań trudnych na ostatnią chwilę, nieadekwatne szacowanie czasu niezbędnego do dobrej realizacji zadania (Dietz, Hofer, Fries 2007;Onwuegbuzie 2004;Rabin, Fogel, Nutter-Upham 2011;Richardson, Abraham, Bond 2012).…”
unclassified
“…Podejmowane były próby wyjaśnienia zachowań prokrastynacyjnych przez określenie związku między samoregulacją a poczuciem własnej skuteczności (Park, Sperling 2012), ale wyniki okazały się niejednoznaczne. Niektórzy badacze ustalili wprawdzie, że studenci wykazujący się wysokim poziomem samoregulacji charakteryzowali się jednocześnie wysokim poczuciem własnej skuteczności, byli aktywni naukowo, potrafili ustalać cele zadaniowe i konsekwentnie dążyć do ich realizacji (Pintrich 2000;Stell 2007).…”
unclassified